Ethiopia’s Great Run : The Growth Acceleration and How to Pace It - World Bank Group (World Bank, Washington, DC, 2015)
This report addresses two questions: what explains Ethiopia’s growth acceleration?; and how can it be sustained? In brief, the authors find that Ethiopia’s rapid economic growth, concentrated in agriculture and services, was driven by substantial public infrastructure investment and supported by a conducive external environment. To sustain high growth, three policy adjustments are presented: identifying sustainable ways of financing infrastructure, supporting private investment through credit markets, and tapping into the growth potential of structural reforms.